2017
DOI: 10.1038/npp.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Role of κ-Opioid Receptors in the Bed Nucleus of Stria Terminalis in Reinstatement of Alcohol Seeking

Abstract: κ-Opioid receptors (KORs) and their endogenous ligand dynorphin are involved in stress-induced alcohol seeking but the mechanisms involved are largely unknown. We previously showed that systemic injections of the KOR agonist U50,488, which induce stress-like aversive states, reinstate alcohol seeking after extinction of the alcohol-reinforced responding. Here, we used the neuronal activity marker Fos and site-specific injections of the KOR antagonist nor-BNI and U50,488 to study brain mechanisms of U50,488-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 88 publications
3
25
0
Order By: Relevance
“…Various stress‐related neuromodulatory and neuropeptide systems, including CRF, noradrenaline, dynorphin, and pituitary adenylate cyclase‐activating peptide (PACAP) act within the BNST to affect stress‐induced reinstatement of reward‐seeking (Di Bonaventura et al, ; Erb, Salmaso, Rodaros, & Stewart, ; Erb & Stewart, ; Lê, Funk, Coen, Tamadon, & Shaham, ; Leri, Flores, Rodaros, & Stewart, ; Miles et al, ; Vranjkovic, Gasser, Gerndt, Baker, & Mantsch, ; Wang, Fang, Liu, & Lu, ). We have recently discovered a role for the neuropeptide system relaxin‐3 and its cognate receptor, relaxin family peptide receptor 3 (RXFP3), in stress‐induced relapse to alcohol seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Various stress‐related neuromodulatory and neuropeptide systems, including CRF, noradrenaline, dynorphin, and pituitary adenylate cyclase‐activating peptide (PACAP) act within the BNST to affect stress‐induced reinstatement of reward‐seeking (Di Bonaventura et al, ; Erb, Salmaso, Rodaros, & Stewart, ; Erb & Stewart, ; Lê, Funk, Coen, Tamadon, & Shaham, ; Leri, Flores, Rodaros, & Stewart, ; Miles et al, ; Vranjkovic, Gasser, Gerndt, Baker, & Mantsch, ; Wang, Fang, Liu, & Lu, ). We have recently discovered a role for the neuropeptide system relaxin‐3 and its cognate receptor, relaxin family peptide receptor 3 (RXFP3), in stress‐induced relapse to alcohol seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from repeated stress, BNST KOR have been heavily implicated in models of ethanol dependence. For example, intra-BNST KOR antagonism reduces EtOH binge-like drinking in the dark (Haun et al 2020) and stress-induced reinstatement for alcohol seeking (Lê et al 2018).…”
Section: Utility Of Kor Antagonists For Stress Management Related To mentioning
confidence: 99%
“…Stressors such as forced swim stress can increase KOR phosphorylation in the BNST, a marker of dynorphin release (Land et al 2009, Bruchas et al 2007. KORs in the BNST also appear to mediate interactions between stress and alcohol drinking, as BNST norBNI attenuates stress-induced alcohol seeking (Lê et al 2018) and reduces alcohol withdrawal-induced 22-kHz ultrasonic vocalizations (Erikson et al 2018). Our laboratory and others have shown that neuropeptide circuits in the BNST are critical for anxiety-like behavior, stress-related behavior, and stress behaviors affected by alcohol drinking (Bruchas et al 2009, Crowley et al 2016, Giardino et al 2018, Hwa et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…1C], suggestive of maladaptive survival behavior. Previous studies have shown that activation of the dynorphin (Pdyn)/KOR system can modulate stress- 20 induced EtOH seeking (7), so we tested if KOR blockade could alter drinking-induced stress behavior. Systemic treatment with 5 mg/kg of the long-acting KOR antagonist norBNI rescued the EtOH-induced impairment of predator odor response [ Fig.…”
Section: Main Textmentioning
confidence: 99%